A modeling of electricity generation by using geothermal assisted organic Rankine cycle with internal heat recovery - Canbolat, A. S.; Bademlioğlu, Ali Hüsnü; Kaynakli, O. (Taylor & Francis Inc, 2023)
In this study, the performance of organic Rankine cycle (ORC), which produces electrical energy, was examined by using a geothermal resource with a temperature of 145 degrees C. The fluids used in the system were determined as dry type fluids, and R142b, R227ea, R245fa, R600, and R600a were preferred as a working fluid. Within the scope of this study, energy and exergy analysis of the system was performed for different evaporator pressures (1000-2000 kPa). With the help of these analyses, the performances of the cycle elements were examined and the first and second law efficiencies of the system were compared for different refrigerants. Considering the selection of refrigerant, and evaporator pressure within the scope of this study, the first and second law efficiencies of the cycle have enhanced maximum of 4.86% and 19.78%, respectively.
Keywords: organic Rankine cycle; energy and exergy analysis; geothermal; internal heat recovery; refrigerant